(3GdeSGdc aj TQM GdehWCs - (3eMeO Hf YHO Gddg Hf eMeO GdeYGaQj GdETHjdj GdeGdcj, GdbGVj CHh HcQ GHf GdYQHqj , J (B543 (3g` s; (3GdGeGe eGdc , eGdc Hf CfS Hf eGdc GdGUHMj,J (B179 (3g` s ((3YeQ Hf jhSa GdafGfi s)
(3ChdgG (B:s
(3bGd GdEeGe GdMGaX CHh HcQ Hf GdYQHi cJGH GdLgGO hCMcGeg hajg KdGK eSGFd (B: (3GdChdi ai GTJbGbg dI s
(3BNQgG (B:s
(3jfJgi HGdcdGe Ydi CSeGA GdfHi Ydjg GdUdGI hGdSdGe hBNQ eG ajg (B: (3hCfG GYJPQ Edi cd ef fXQ ajg ChbQCg Ch JUaMg hGdMeO ddg QH GdYGdejf s
(3GdfSNI HgG MhGTs
(3bQf GdfSN (B:s
(3GdbQf GdKGefs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B5 - (3U (B257 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B8 - (3U (B168s
(3JHUQGJ GdCUd (B:s
Keywords: (3GdMOjK h GdeUWdMs